Algo más que piedra y consignas: agitación social vista desde la prensa durante el gobierno de la concentración nacional (1930 1934) (2009)
This article is a partial advance of the investigation about the social protest in Colombia during the liberal republic (1930 - 1946), in which it is carried out a general and descriptive examination of some social groups involved in the actions of inconformity, the modalities of protest adoptedas them, their demands or requirements and the spatial location of the snaps during the administration of the president Enrique Olaya Herrera based on information of press, for which it was statistical elementary grouping in tables and graphs.